Embryonic stem cell‐derived haematopoietic progenitor cells down‐regulate the CD3 ξ chain on T cells, abrogating alloreactive T cells. Issue 3 (July 2014) - Kim, Eun‐Mi; Miyake, Bob; Aggarwal, Manish; Voetlause, Ruth; Griffith, Maia; Zavazava, Nicholas
Summary Murine embryonic stem (ES) cell‐derived haematopoietic progenitor cells (HPCs) engraft and populate lymphoid organs. In vivo, HPCs engraft across MHC barriers protecting donor‐type allografts from rejection. However, the underlying phenomenon remains elusive. Here, we sought to determine the mechanism by which ES cell‐derived HPCs regulate alloreactive T cells. We used the 2C mouse, which expresses a transgenic T‐cell receptor against H2‐Ld to determine whether HPCs are deleted by cytotoxic T lymphocytes (CTLs). Previously, we reported that HPCs express MHC class I antigens poorly and do not express class II antigens. In vitro stimulated 2C CTLs failed to lyse H2‐Ld HPCs in a standard 4‐hr 51chromium release assay. Similarly, when the HPCs were tested in an ELISPOT assay measuring the release of interferon‐γ by CTLs, HPCs failed to induce CTL degranulation. In addition, mice that were injected with HPCs showed a marked decrease in T‐cell responses to alloantigen and CD3 stimulation, but showed a normal response to PMA/ionomycin, suggesting that HPCs impaired T‐cell signalling through the T‐cell receptor/CD3 complex. Here, we show that HPCs secrete arginase, an enzyme that scavenges l‐arginine, leading to metabolites that down‐regulate CD3 ζ chain. Indeed an arginase inhibitor partially restored expression of the CD3 ζ chain, implicating arginase 1 in the down‐regulation of T cells. This previously unrecognized property of ES cell‐derived HPCs could positively enhance the engraftment of ES cell‐derived HPCs across MHC barriers by preventing rejection.